Etika komunikasi public relation dalam menjaga citra perusahaan - Rohmah, Sabana Nur (Maliki Interdisciplinary Journal, 2025)
Public Relations (PR) communication ethics are the moral foundation that determines the quality of the relationship between a company and the public. In the modern business context, corporate image is a strategic factor in building public trust and organizational competitiveness. This study aims to examine in depth how the application of communication ethics in PR practices plays a role in maintaining a company’s image, especially when facing crises and challenges in the digital era. This study uses a descriptive qualitative method based on literature analysis from several relevant national journals. The results show that the application of PR communication ethics encompasses the principles of honesty, transparency, social responsibility, and respect for the public as communication partners. Ethical PR practices not only function to avoid reputational crises but also to create long-term relationships based on trust. In the fast-paced digital era, ethical challenges are increasingly complex, encompassing issues of privacy, information manipulation, and the use of artificial intelligence-based technology. Therefore, PR practitioners need to develop ethical awareness, strengthen professional integrity, and adapt communication strategies to align with universal moral values ​​and increasing public expectations.